Hollow N-doped Carbon Polyhedrons with Hierarchically Porous Shell for Confinement of Polysulfides in Lithium–Sulfur Batteries - Yang, Dong-Hui; Zhou, Hang-Yu; Liu, Hu; Han, Bao-Hang (iScience, 2019)
Herein, hollow N-doped carbon polyhedrons with hierarchical pores were fabricated by etching ZIF-8 crystals and were first used as the host of sulfur for lithium-sulfur batteries. This host possesses both micropores and mesopores, and inner wide cavities, which enable the sulfur to effectively immerse into the polyhedrons without obstacles and simultaneously restrict the escaping of polysulfides by outer carbon shell and abundant N sites. Hence, the polyhedron host combines the physical confinement and chemical interaction for polysulfides by virtue of the unique architecture. As a result, the hierarchically porous polyhedron enables a sulfur content of 72 wt% and achieves a faster polysulfide trapping and better electrochemical performance than the ZIF-8-derived microporous host at the sulfur loading of 1 and 5 mg cm−2. [Display omitted] •A hollow N-doped carbon polyhedron is newly developed as sulfur host•The host provides both physical confinement and chemical interaction for polysulfides•The host displays a fast polysulfide trapping by hierarchical pores•The host enables a high sulfur loading and achieves better electrochemical performance Energy Storage; Polymers; Energy Materials